Molecular biology of viruses - Easton, Andrew (Henry Stewart Talks, 2009)
Definition of a virus, The chemical and physical nature of virus genomes, The Baltimore classification scheme for viruses, The control of transcription of gene viruses, Reliance on host ribosomes, Virus genome replication, RNA virus genomes